Intervention Instruments in the Implementation of Public Policies - Florina POPA (Communications of International Proceedings, 2022)
In formulating public policy, the proposed objectives are pursued and State intervention instruments are used. The intervention instruments that governments use to implement public policies are known as the mechanisms by which the State intervenes to face a number of challenges, such as: reducing bureaucracy, decentralization, increasing the quality of institutions' activity. The pursued aim of the present paper is getting through some theories regarding intervention instruments of public policy for categorization, from the perspective of their definition and of the presentation of a typology of intervention instruments, as reflected in the specialty literature. The objectives of the paper are: description of notions with reference to the definition of intervention instruments of public policies and emphasizing the relevance of some categories of intervention instruments, as developed in the specialty literature. The conclusions shall retain the essence of the aspects studied during the work and shall underlie the results of the research. The methodology used is the documentation from foreign and domestic specialty literature, holding, synthetizing and processing of ideas, through the author's own interpretation. The reason for choosing this methodology was the very nature of the subject approached in the paper, namely, the theoretical approach, but also the wealth of information that can be found in foreign and domestic specialty literature.
Keywords: public policies; instruments; mechanisms; implementation; definitions.